Strengthening Anti-Bullying Values Through Education and Social Campaigns at SMPN 7 Kota Bangun: Penguatan Nilai Anti-Perundungan Melalui Edukasi dan Kampanye Sosial di SMPN 7 Kota Bangun - Ahmad Jailani; Muhammad Gibran Alza; Alda Rizki Aulia; Hanif Al Farisy; Khansa Aprillia Zahra; Sindi Fatimah; Nicko Wardhana; Muhammad Yoga Adhi Pramana; Nadirah; Dela Juliarsih Rahman; Islamudin Ahmad (Jurnal Abdita Naturafarm, 2026)
This study aims to strengthen anti-bullying values through education and social campaigns at SMPN 7 Kota Bangun. The method applied was a social campaign using presentations, interactive discussions, and educational posters, followed by evaluation through a post-test. The post-test results revealed that the majority of students understood that bullying, both physical and non-physical, negatively affects social relationships and the learning environment. Students also emphasized the importance of sanctions for perpetrators, the obligation to help peers, and the shared responsibility of the school community in preventing bullying. However, some students still held misconceptions that bullying is only dangerous if it is physical. Campaign documentation illustrated students’ active engagement during socialization sessions, the use of posters as media, and a spirit of solidarity in supporting anti-bullying values. Challenges encountered included limited time and students’ hesitation to report cases, while solutions proposed involved continuous campaigns, teacher involvement, and peer-to-peer approaches. Therefore, this program has proven effective in strengthening awareness and anti-bullying values, although further efforts are needed to ensure a more sustainable impact.